2020
DOI: 10.5001/omj.2020.107
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Smoking Prevalence, Health Risk, and Cessation in the UAE

Abstract: Objectives Tobacco smoking is a major public health concern and a leading cause of preventable death. We sought to review epidemiological studies available on the prevalence of tobacco use, the associated health effects, and interventions that have undergone evaluation concerning smoking cessation and prevention in the UAE. Methods An electronic search of the PubMed and Scopus databases was conducted using appropriate keywords for articles published between 2007 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Due to government led programs to curb the smoking rates in the UAE currently, the prevalence of smoking in UAE is less compared to other countries in the Middle East. 14 Studies show that lipid lowering plays and important role in the control of ASCVD risk. The patients in this study would benefit from significant lipid lowering therapy to reduce their risk of ASCVD.…”
Section: Resultsmentioning
confidence: 99%
“…Due to government led programs to curb the smoking rates in the UAE currently, the prevalence of smoking in UAE is less compared to other countries in the Middle East. 14 Studies show that lipid lowering plays and important role in the control of ASCVD risk. The patients in this study would benefit from significant lipid lowering therapy to reduce their risk of ASCVD.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] Studies in the UAE have shown that approximately two-thirds of Emirati women were classified as overweight or obesity; however, these cross-sectional designs were unable to elucidate the risk factors for weight gain. 17,18 Due to the cultural practices and religious beliefs of women in the UAE, the prevalence of tobacco smoking 19 and alcohol consumption is extremely low. 17 However, a birth cohort of Emirati and Arab women in the UAE reported that more than half of women with overweight or obesity, and almost three-quarters of pregnant women had inadequate and excessive GWG.…”
Section: Introductionmentioning
confidence: 99%